To simplify the equation \( 2(x−5)=9−3x+6+8+3x+7 \), we will go through each side separately.
Left Side:
Using the Distributive Property on the left side: \[ 2(x - 5) = 2x - 10 \]
Right Side:
Now, let's simplify the right side by combining like terms: \[ 9 - 3x + 6 + 8 + 3x + 7 \] First, combine the constant terms: \[ 9 + 6 + 8 + 7 = 30 \] Next, combine the \( -3x \) and \( 3x \): \[ -3x + 3x = 0 \] Putting this together, the right side simplifies to: \[ 0 + 30 = 30 \]
Responses:
- Left Side Simplified: \( 2x - 10 \)
- Right Side Simplified: \( 30 \)
So the final answers are:
- Simplify the left side of the equation: \( 2x - 10 \)
- Simplify the right side of the equation: \( 30 \)